The great catastrophe: causes of the Permo-Triassic marine mass extinction - Wignall, Paul B; Bond, David P G (National Science Review, 2023)
The marine losses during the Permo-Triassic mass extinction were the worst ever experienced. All groups were badly affected, especially amongst the benthos (e.g. brachiopods, corals, bryozoans, foraminifers, ostracods). Planktonic populations underwent a fundamental change with eukaryotic algae being replaced by nitrogen-fixing bacteria, green-sulphur bacteria, sulphate-reducing bacteria and prasinophytes. Detailed studies of boundary sections, especially those in South China, have resolved the crisis to a ∼55 kyr interval straddling the Permo-Triassic boundary. Many of the losses occur at the beginning and end of this interval painting a picture of a two-phase extinction. Improved knowledge of the extinction has been supported by numerous geochemical studies that allow diverse proposed extinction mechanisms to be studied. A transition from oxygenated to anoxic-euxinic conditions is seen in most sections globally, although the intensity and timing shows regional variability. Decreased ocean ventilation coincides with rapidly rising temperatures and many extinction scenarios attribute the losses to both anoxia and high temperatures. Other kill mechanisms include ocean acidification for which there is conflicting support from geochemical proxies and, even less likely, siltation (burial under a massive influx of terrigenous sediment) which lacks substantive sedimentological evidence. The ultimate driver of the catastrophic changes at the end of the Permian was likely Siberian Trap eruptions and their associated carbon dioxide emissions with consequences such as warming, ocean stagnation and acidification. Volcanic winter episodes stemming from Siberian volcanism have also been linked to the crisis, but the short-term nature of these episodes (<decades) and the overwhelming evidence for rapid warming during the crisis makes this an unlikely cause. Finally, whilst the extinction is well studied in equatorial latitudes, a different history is found in northern Boreal latitudes including an earlier crisis which ...